ANALISIS PENGARUH MODAL, BAHAN BAKU, UPAH TENAGA KERJA DAN HARGA PRODUK TERHADAP PENDAPATAN PENGUSAHA INDUSTRI KERAJINAN BATAKO DI KABUPATEN BADUNG - Ida Ayu Gede, Sri Purnama Sari; Ketut, Sutrisna (PIRAMIDA, 2019)
Handicraft industry has a very important role in Bali in general and in Badung regency especially in providing employment opportunities for the community. The purpose of this study was to determine the effect of capital, raw material, wages and product price to the brick handicraft industry in revenue Badung regency. The method used is observation, structured interviews, and in depth interviews. This study used a technique sampling jenuh with 61 samples of entrepreneur of brick handicraft industry. Data were analyzed with multiple linear regression. The analysis showed that, simultaneously variable capital, raw material, wages and product price experience a significant effect on the revenue of brick handicraft industry. Determination coefficient of 80,3 percent, which means a variation or fluctuation revenue of entrepreneur of brick handicraft industry in Badung regency simultaneously influenced by the independent variables (capital, raw material, wages and product price capital). In partial capital, raw material, wages and product price positive and significant effect on the revenue of entrepreneur of brick handcraft industry in the Badung regency.